Change management within an enterprise-wide packaged software implementation - Forrester, Ian D (My University, 1996)
Investments in information technology have in many cases failed to deliver the anticipated benefits. It is now accepted that real value can only be leveraged by linking IT implementation to organisational change and process redesign. The management of this change is inextricably linked to the overall success of the implementation. The focus of the research was on identifying what the key elements of successful change management were. Research into generic change management was used as a basis for determining these critical success factors. The applicability of these factors in the case of an enterprise wide package software implementation was then tested through a case study method. The research showed that the factors developed were applicable in managing technology driven change. In addition to the factors developed, additional factors were identified as being relevant in the case of packaged software implementations.
A research report submitted to the Faculty of Commerce University of the Witwatersrand, Johannesburg for the Degree of Masters of Commerce
Keywords: Information technology -- Management.; Organizational change.